#PharosComeBack: My MBA Journey as a Designer. (15th November 2021) - Attia, Jomana G.
Abstract : I needed to gain insight into Egyptian business culture that could not be acquired from literature alone. An Egyptian designer ponders her country's history in education as well as her self‐confidence as she navigates getting an MBA.